Social Skills Training for Adolescents With Intellectual Disabilities: A School-Based Evaluation. (July 2016) - O'Handley, Roderick D.; Ford, W. Blake; Radley, Keith C.; Helbig, Kate A.; Wimberly, Joy K.
Individuals with intellectual disabilities (ID) often demonstrate impairments in social functioning, with deficits becoming more apparent during adolescence. This study evaluated the effects of the Superheroes Social Skills program, a program that combines behavioral skills training and video modeling to teach target social skills, on accurate demonstration of three target social skills in adolescents with ID. Skills taught in the present study include Expressing Wants and Needs, Conversation, and Turn Taking. Four adolescents with ID participated in a 3-week social skills intervention, with the intervention occurring twice per week. A multiple baseline across skills design was used to determine the effect of the intervention on social skill accuracy in both a training and generalization setting. All participants demonstrated substantial improvements in skill accuracy in both settings, with teacher ratings of social functioning further suggesting generalization of social skills to nontraining settings.